Poverty and natural resource management in the semi-arid tropics: Revisiting challenges and conceptual iáues - Shiferaw, B.A. (Andhra Pradesh (India), 2002)
Sumario (En)
Ilus.; 45 ref.
Keywords: POBREZA; RECURSOS NATURALES; ZONA TROPICAL; PAISES EN DESARROLLO; AGRICULTURA; DESARROLLOA AGRICOLA; RECURSOS HIDRICOS; DEGRADACION